If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(r + 6) = -37 Reorder the terms: -2(6 + r) = -37 (6 * -2 + r * -2) = -37 (-12 + -2r) = -37 Solving -12 + -2r = -37 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -2r = -37 + 12 Combine like terms: -12 + 12 = 0 0 + -2r = -37 + 12 -2r = -37 + 12 Combine like terms: -37 + 12 = -25 -2r = -25 Divide each side by '-2'. r = 12.5 Simplifying r = 12.5
| 2-2n=n+64 | | 0.33=6 | | 2x^2-10x=6 | | 10x-3=-17 | | (3k-7)/(5)=16 | | 49+1-4c=39c-2 | | 2k+k+4= | | [t+5]+3=12 | | 7-2x=0 | | 6x+8=4x+50 | | 3x+8=8+2x+x | | 729=x^3 | | 4(d-20)=1 | | 245=-7a | | (36-5x)+(36-5x)+4x+4x=x | | 3x+28=7(x+4)-4x | | 2(6+3)=18-3(16-3d) | | 6+12=16 | | x+17=36-x | | x=20-0.5y | | 5=1-2n+5 | | 4(d-5)=1 | | 5m-14=8m+4 | | 2.5x-(-8.2)=26.7 | | -8n+4(1+5)=6n-14 | | -11(x+9)=99 | | 6x^4*3x^4= | | y=-0.80(55)+136 | | 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 | | 6y-7=10y+25 |